Problems and needs of the older adults and their families infected with COVID-19 in the community of Northeastern Thailand: a qualitative study - Hinkaew, ฺBualun; Yodsuban, Pairin; Kasemsuk, Weha; Siripoon, Prakaikaew (Jurnal Ners, 2025)
Introduction: The COVID-19 pandemic has severely impacted older adults, particularly those with chronic illnesses, due to their heightened vulnerability and limited access to care. In Northeastern Thailand, many older adults live alone and face multifaceted health and social challenges. This study aimed to explore the problems and needs of older adults and their families infected with COVID-19 within the social and cultural context of this region. Methods: A qualitative content analysis was conducted using data collected through observations, in-depth interviews, focus group discussions (FGDs), field notes, and participant observations in community settings. A total of 48 informants were purposively selected, including representatives from public and community organizations, health service units, local administrative organizations, local leaders and village headmen, and older adults and their family members who had been infected with COVID-19. Results: The study identified five key themes reflecting the problems and needs of older adults and their families affected by COVID-19. Socially, participants experienced isolation and limited access to support networks. Economic challenges included income loss and insufficient financial assistance. Environmental issues involved inadequate housing and restricted access to essential services. Health-related problems encompassed physical decline and limited healthcare access. Politically and administratively, delays in assistance and ineffective coordination among agencies were reported. Conclusions: Older adults and their families infected with COVID-19 encounter complex and multidimensional challenges. Community nurses play a vital role as health system managers in addressing these needs and ensuring accessible and appropriate primary health care services.